Avaliação de recursos genéticos de milho conservados in situ on farm - Somavilla, Iana (2014)
Corn is one of the most cultivated cereal in Brazil, making the country's third largest producer of culture. Due to their genetic diversity, which allows its adaptation to different environments. Among the cultivars, are local, traditional or creole called (CLTCs), which are an alternative for small farms and also constitute an important source of genetic resistance and tolerance to different types of stress and adaptation to different environments and local managements. This study aimed to evaluate the adaptability and phenotypic stability of 15 Land varieties conserved in Family Seed Banks in Ibarama - RS as well, estimate genetic parameters in sib progenies derived from a field of three recombination Creole cultivars corn. Evaluation of adaptability and stability was performed in two consecutive years and in three areas, totaling six environments, using the randomized block design with three replications of two lines of 5m spacing of 0.9 m between rows and 0.2 m between plants. Productivity data were evaluated by the proposed Eberhart and Russell (1966) method. Among the cultivars stood out Cinquentinha with adaptability to harsh environments and to Sertanejo favorable and the others were considered wide adaptability. As for stability, all landraces cultivars showed high stability and predictability of production. For estimation of genetic parameters, three cultivars of yellow endosperm in order to reduce plant height were recombined. The progenies were recombined into three environments in randomized block design, with rows of 5m length and spacing of 0.9 m between rows and 0.2 m between plants. Heritability, phenotypic variance, genotypic and environmental and Cve / CVG: characteristics such as plant height, plant height and ear height and productivity for each of these characteristics were estimated using the GENES (Cruz, 1997) the following genetic parameters were evaluated program . The selection in sib progenies of creole maize in order to reduce the size of the plant is related to the selection of plants with lower ear height and these progenies have potential and wide genetic variability for the improvement of the characters plant height, height of spike and grain yield in the present study, by genetic selection gains can be expected.